Associations between maternal physical activity in early and late pregnancy and offspring birth size: remote federated individual level meta‐analysis from eight cohort studies. (22nd October 2018) - Pastorino, S; Bishop, T; Crozier, SR; Granström, C; Kordas, K; Küpers, LK; O'Brien, EC; Polanska, K; Sauder, KA; Zafarmand, MH; Wilson, RC; Agyemang, C; et al.
Abstract : Objective: Evidence on the impact of leisure time physical activity (LTPA) in pregnancy on birth size is inconsistent. We aimed to examine the association between LTPA during early and late pregnancy and newborn anthropometric outcomes. Design: Individual level meta‐analysis, which reduces heterogeneity across studies. Setting: A consortium of eight population‐based studies (seven European and one US) comprising 72 694 participants. Methods: Generalised linear models with consistent inclusion of confounders (gestational age, sex, parity, maternal age, education, ethnicity, BMI, smoking, and alcohol intake) were used to test associations between self‐reported LTPA at either early (8–18 weeks gestation) or late pregnancy (30+ weeks) and the outcomes. Results were pooled using random effects meta‐analyses. Main outcome measures: Birth weight, large‐for‐gestational age (LGA), macrosomia, small‐for‐gestational age (SGA), % body fat, and ponderal index at birth. Results: Late, but not early, gestation maternal moderate to vigorous physical activity (MVPA), vigorous activity, and LTPA energy expenditure were modestly inversely associated with BW, LGA, macrosomia, and ponderal index, without heterogeneity (all: I 2  = 0%). For each extra hour/week of MVPA, RR for LGA and macrosomia were 0.97 (95% CI: 0.96, 0.98) and 0.96 (95% CI: 0.94, 0.98), respectively. Associations were only modestly reduced after additional adjustments for maternal BMI and gestational diabetes. No measure of LTPA was associated with risk for SGA. Conclusions: Physical activity in late, but not early, pregnancy is consistently associated with modestly lower risk of LGA and macrosomia, but not SGA. Tweetable abstract: In an individual participant meta‐analysis, late pregnancy moderate to vigorous physical activity modestly reduced birth size outcomes. Tweetable abstract: In an individual participant meta‐analysis, late pregnancy moderate to vigorous physical activity modestly reduced birth size outcomes.